Perry Belmont papers - Belmont, Perry, 1850-1947.
Correspondence (chiefly 1900), account books (1775-1827), stock transfer book (1816-1822) of the Loudon Company (Va.), scrapbooks, and pamphlets. The small number of letters are concerned mostly with politics and the possible presidential candidacy of Admiral Dewey.
Lawyer, author, diplomat, and U.S. representative from New York.
Collection material in English.
Keywords: Dewey, George, -- 1837-1917.; Loudon Company (Va.); Representatives, U.S. Congress -- New York (State)